PTU-059 Comparison Of Bipolar Radiofrequency Cutting And Mono Polar Cutting For Endoscopic Submucosal Dissection (esd) In A Porcine Model. (9th June 2014) - Tsiamoulos, ZP; Hancock, C; Sibbons, PD; Saunders, BP
Abstract : Introduction: Current endoscopic knives utilise mono-polar energy to incise the mucosa, dissect the submucosa and coagulate bleeding vessels. Monopolar devices have proven efficacy but remain technically challenging to use with the risk of major complications. Methods: A new bipolar endoscopic device "Speedboat-RS2, (S-RS2) Creo Medical Ltd, UK" was compared to a standard mono-polar endoscopic device (Flush-knife-BT/F-BT/Fujifilm, Japan) for endoscopic submucosal dissection (ESD) in the porcine colon. The S-RS2 blade delivers bipolar radio frequency (RF-400 KHz) cutting and microwave coagulation (5.8 GHz) for hemostasis, and contains a retractable needle for submucosal injection/tissue irrigation. It also has an insulated hull to prevent thermal injury to the underlying muscle layer. ESD was performed in a random order and video recorded on 5 consecutive 60kg pigs. The following parameters were measured: time taken to complete resection, complications encountered and histological assessment. Two animals were recovered for one week and four animals for four weeks. Results: Ten consecutive resections were performed in the colorectum (2 per animal), 5 with S-RS2 and 5 with F-BT. Median time for S-RS2 to complete a resection was 44 min using RF cutting 30W, and for F-BT was 52min using monopolar cutting for mucosal incision (80W) and for submucosal dissection, monopolar forced coagulation 30W. Median flap size for S-RS2 was 36.8mm and for F-BT was 43mm. Microwave coagulation was applied for either minor bleeding or visible vessels on 25 occasions with S-RS2. Monopolar coagulation was applied 14 times with F-BT, mean energy 30W. The Hemostatic Coagrasper was used 7 times to control arteriolar bleeding during S-RS2 dissection when microwave was not sufficient and only once during Flushknife-RS2 dissection. Endoclips were placed to treat deep muscle injury in the resection base on 10 occasions in the F-BT resections (15clips placed) and on 3 occasions (3 clips) for the S-RS2 resections. There was only one study perforation – F-BT group, where urgent peritoneal decompression was required and the resection was abandoned. Histology (S-RS2 resections) showed an intact muscle layer in four resection bases and in one there was slight muscle alteration but muscle cell viability was retained. The muscle layer was absent in two F-BT resection bases and moderately altered in one. Conclusion: Compared to Flush knife-BT ESD colonic resections (monopolar) the Speedboat-RS2 was was associated with less muscle injury and need for endoscopic clipping. However Speedboat-RS2 resections produced more intraprocedural bleeding requiring the haemostatic forceps. Disclosure of Interest: Z. Tsiamoulos Consultant for: Creo Medical Ltd, C. Hancock Shareholder of: Creo Medical Ltd, P. Sibbons Paid instructor for: Creo Medical Ltd, B. Saunders Consultant for: Creo Medical Ltd, Paid instructor for: Olympus KeyMed.